1995
DOI: 10.1177/000331979504600707
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Thermoregulation in Raynaud's Phenomenon

Abstract: subjects with RP had significantly lower blood flow at all stages of the test; moreover, their digital rewarming response following central cooling was considerably prolonged when compared with controls. Body temperature was lower and dropped significantly more in the RP group following the cold challenge. The authors conclude that subjects with RP have an impaired thermoregulatory mechanism. This may partially explain cold sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…24 Greenstein et al reported that subjects with Raynaud's phenomenon have an impaired thermoregulation, which they suggest to explain the cold sensitivity in this patient group. 38 In this study, we found abnormal rewarming in both healthy subjects and patients. Second, we found no relationship between rewarming patterns after cold stress testing in patients with cold intolerance recovering from a hand fracture and subjective cold intolerance.…”
Section: Discussionmentioning
confidence: 50%
“…24 Greenstein et al reported that subjects with Raynaud's phenomenon have an impaired thermoregulation, which they suggest to explain the cold sensitivity in this patient group. 38 In this study, we found abnormal rewarming in both healthy subjects and patients. Second, we found no relationship between rewarming patterns after cold stress testing in patients with cold intolerance recovering from a hand fracture and subjective cold intolerance.…”
Section: Discussionmentioning
confidence: 50%
“…Unfortunately, CS was not investigated in that study. Other studies have shown that patients with RP show a decreased perfusion of fingers during cold exposure [35] and have an increased risk of contracting cold injuries [36]. As described above, ischemic effects on peripheral nerves might then serve as an explanation for CS in heavily cold-exposed subjects with RP.…”
Section: Interpretation and Comparisonmentioning
confidence: 89%
“…Indeed, patients with primary and secondary RP have lower baseline CVC compared with controls (4,14,28). As temperature plays a key role in baseline flux, standardizing baseline skin temperature when performing microvascular reactivity improves reproducibility, especially when expressing data as a function of baseline (26,27).…”
Section: Discussionmentioning
confidence: 99%